2021
DOI: 10.1002/clen.202000401
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Carbon Nanotubes‐Silica Binary Composite for Effective Pb(II) Sequestration from Industrial Effluents: Multivariate Process Optimization

Abstract: In this work, magnetic multiwalled carbon nanotubes‐silica binary composite (mCNT@APS) is synthesized via amide bond and utilized for the Pb(II) adsorption from aqueous solutions in batch mode. The composite is characterized using Fourier transform infrared spectroscopy (FT‐IR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), energy‐dispersive X‐ray spectroscopy (EDS), transmission electron microscopy (TEM), X‐ray diffraction (XRD), and point of zero charge (pHpzc) studies. Three levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…In this paper, the studies on the optimization of TC removal and multiwall carbon nanotube (MWCNTs) adsorption process by RSM-BBD were summarized, which were recorded in Tables S2 and S3. Table S2 [54][55][56][57] and Table S3 [ [58][59][60][61][62][63][64][65][66] showed that BBD could improve adsorption efficiency and save resources in the fields of MWCNTs adsorbent and TC removal, respectively [54,58]. At present, RSM-BBD optimization of MMWCNTs adsorption TC needs further practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the studies on the optimization of TC removal and multiwall carbon nanotube (MWCNTs) adsorption process by RSM-BBD were summarized, which were recorded in Tables S2 and S3. Table S2 [54][55][56][57] and Table S3 [ [58][59][60][61][62][63][64][65][66] showed that BBD could improve adsorption efficiency and save resources in the fields of MWCNTs adsorbent and TC removal, respectively [54,58]. At present, RSM-BBD optimization of MMWCNTs adsorption TC needs further practice.…”
Section: Introductionmentioning
confidence: 99%